Perkembangan pada Masa Sekolah Anak Usia 6-12 Tahun - Lubis, Ramadan; Asyura, Asyura; Zywetta, Aurora; Al-Saudia, Nadhira; Aisah, Nazmi; Rezky, Rita; Rambe, Siti Sarah (MODELING: Jurnal Program Studi PGMI, 2024)
This research explores the development of children aged 6-12 years at school. This study aims to understand the developments that occur during the school years of children aged 6-12 years. The research method used was in-depth interviews conducted by a mini research group. The results of mini research revealed that Irham had experienced physical development at the age of 12 years. This development starts with increasing weight and height, then changes teeth, brain growth and psychomotor development. Then they are able to carry out physical and psychomotor development activities such as writing, drawing and coloring. Emotional development in Irham is also able to express and control his emotions through imitation and habituation. Social development: Irham is able to socialize and interact with the surrounding community. In his moral development, Irham was able to distinguish between good and bad. In terms of educational implications, he is able to think normally in lessons at school.